Implementable Mechanisms for discrete utility functions, a solution using Tropical Geometry (2019)
For mechanisms with two possible outcomes and a unique agent with two posible types, we state sufficient and necessary conditions over the type space that guarantees the existence of an incentive compatible mechanism. By using tropical geometry, we found that these conditions rely only on the relative valuations to be increasing over types. This result extends implementability for discrete utility functions.